Depression in patients with multiple sclerosis. The prevalence, diagnostic challenges and evidence-based treatment methods - Cezary Michał Wegenko; Hanna Sitka; Magdalena Czaja; Julia Kuźniar; Patrycja Kozubek (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Gradual progression of cognitive and physical disability negatively affects personal, social and economic well-being of patients with multiple sclerosis. This particular group of people has a high risk of developing depressive disorders. This study reviews the prevalence, current diagnostic tools and evidence-based methods of treating depression in patients suffering from MS.